2016
DOI: 10.1515/advgeom-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Framed curves in the Euclidean space

Abstract: A framed curve in the Euclidean space is a curve with a moving frame. It is a generalization not only of regular curves with linear independent condition, but also of Legendre curves in the unit tangent bundle. We de ne smooth functions for a framed curve, called the curvature of the framed curve, similarly to the curvature of a regular curve and of a Legendre curve. Framed curves may have singularities. The curvature of the framed curve is quite useful to analyse the framed curves and their singularities. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 5 publications
0
92
0
Order By: Relevance
“…Note that this curve is not a frontal (see [4,6]). However, we can construct a framed curve , 1)) by using the method in the proof of Theorem 1.2, since the singular set Σ(γ) = {0} and the limit of the derivatives of the tangent vectors exists at the origin.…”
Section: Example 31 Letmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this curve is not a frontal (see [4,6]). However, we can construct a framed curve , 1)) by using the method in the proof of Theorem 1.2, since the singular set Σ(γ) = {0} and the limit of the derivatives of the tangent vectors exists at the origin.…”
Section: Example 31 Letmentioning
confidence: 99%
“…We have shown that analytic curves are at least locally framed base curves in the cases of plane curves (n = 2) and space curves (n = 3), see [4] and [6], respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let R 3 be the three-dimensional Euclidean space, and let γ : I → R 3 be a curve with singular points. In order to investigate this curve, we will introduce the framed curve (cf., [14]). We denote the set ∆ 2 as follows:…”
Section: Framed Curve and Adapted Framementioning
confidence: 99%
“…If space curves have singular points, the Frenet frames of these curves cannot be constructed. However, S. Honda and M. Takahashi [14] gave the definition of framed curves. Framed curves are space curves with moving frames, and they may have singular points.…”
mentioning
confidence: 99%